If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) = 7 Reorder the terms: 6(-2 + x) = 7 (-2 * 6 + x * 6) = 7 (-12 + 6x) = 7 Solving -12 + 6x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = 7 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 7 + 12 6x = 7 + 12 Combine like terms: 7 + 12 = 19 6x = 19 Divide each side by '6'. x = 3.166666667 Simplifying x = 3.166666667
| 36/9=3x+2(-5x) | | -3x+1-7x=1 | | 31.4=2*3.14*r | | 8y+9=120 | | y-13y= | | x+3+5=9 | | 2n^2+2n-40= | | 12n-4-11n+13=13 | | 22=2*3.14*r | | 8+15=1000 | | 48+13m=295 | | 3(p+4)-4p+8(p+1)=90 | | 32n-104=152 | | 6p+15=21 | | 3m+4+7m+5= | | 4m+5.25=43.25 | | 24x-x^2-80=0 | | 10+4y+6y+9= | | 23-a=15 | | y^3-8y=0 | | 8x-8t=3 | | 3p+3=6 | | x^3-12x-2=0 | | -5+2ln(3x)=5 | | 5k^2+50k+300= | | 11x-7y=17 | | 3x^3-36x-6=0 | | 3x^4+8x^3-5x^2+16x-5=0 | | 7/2+1/2X=3X+3/2+5/2X | | B+12=25 | | x-5/3-4=x-1/2 | | 13=5z |